Pendidikan dan Pelatihan Kesehatan Gigi dan Mulut di SD Negeri 01 Ciambar, Sukabumi, Jawa Barat - Livia Kurniawan, Florencia; Lestari, Sri; Yusra, Yohana; Tri Oka Binartha, Ciptadhi; Komariah; Fibryanto, Eko (JURNAL ABDIMAS KESEHATAN TERPADU, 2025)
SD Negeri 01 Ciambar, Sukabumi, West Java, is one of the schools that has quite a large number of students with diverse social and economic backgrounds. Based on initial observations, many students lack awareness of the importance of maintaining dental and oral health. In addition, teachers also need to improve their understanding in guiding students to be able to apply good habits in maintaining dental and oral hygiene. The method used in this activity consists of several stages as follows: observation and identification of problems with initial observations carried out to determine the condition of students' dental and oral health and their level of understanding of dental care and interviews with teachers were conducted to determine the extent of their role in educating students about dental and oral health. Overall, this program succeeded in increasing the awareness and behavior of students and teachers of SDN 01 Ciambar in maintaining dental and oral health. It is hoped that with ongoing education, these good habits can become part of a healthy lifestyle culture in the SDN 01 Ciambar school environment. This program proves that participatory-based education and training supported by interesting methods can increase the awareness and habits of students and teachers in maintaining dental and oral health. The sustainability of the program can be improved with the support of school facilities, routine check-ups by medical personnel, and parental involvement in building a healthy lifestyle culture from an early age.